Keanekaragaman Spesies Bambusa (Poaceae, Bambusoideae) di Kalimantan, Indonesia - Anne Kusumawaty; I Putu Gede P. Damayanto (LPPM Universitas Terbuka, 2024)
Bamboo is reported to have many benefits, including as handicraft material, fishing, building materials, household appliances, furniture, food containers, medicines, vegetable materials, and firewood. In Indonesia, bamboo species richness is quite high with 175 bamboo species that can be found spread from Java to Papua. Research information on Bambusa species data in the Kalimantan region is relatively scarce and invalid. The research aims to provide data on the diversity of Bambusa species in Kalimantan. The research method was carried out descriptively by observing morphological characters from herbarium specimens and digital herbarium. Data were collected from herbarium specimens of bamboo genus Bambusa collected from Kalimantan and digital specimen data stored in online database portals, such as GBIF and Bioportal. All specimens were re-identified and their names validated. The results showed that there are five species of Bambusa in Kalimantan, namely Bambusa glaucophylla Widjaja, B. multiplex (Lour.) Raeusch. ex Schult.f., B. spinosa Roxb., B. tuldoides Munro, and B. vulgaris Schrad. The presentation is complemented by identification keys and explanations.